A ágora digital, a competência crítica em informação e a cidadania ampliada: uma construção possível - Brisola, Anna Cristina Caldeira de Andrada Sobral (2016)
This research tries to draw a path to the discussion of the critical literacy This research tries to draw a path to the discussion of the critical in digital agora, wandering through the concepts involved in this subject. TTo reach the relevant aspects to the Science of Information regarding this literacy is necessary to understand the agora, the citizenship, the qualities of an engaged citizen, the digital media and the digital social networks, as well as the influences that act on both the citizen and the networks. It is needed to understand democracy and the social movements, in addition to understanding what is the digital inclusion and literacy, proficiency in information, critical literacy and literacy for expanded citizenship. The greater goal is to think about how to awaken a taste for information and for the construction of knowledge to the point of stimulating the practice of a participating citizenship. Many authors were needed to walk along this path. It is a long path, but it is essential to the Science of Information and its responsibility, as it's about collaborating in the shaping of the knowledge of the citizen that live in this contemporary cyber world.